Rare variants in SOS2 and LZTR1 are associated with Noonan syndrome. Issue 6 (20th March 2015) - Yamamoto, Guilherme Lopes; Aguena, Meire; Gos, Monika; Hung, Christina; Pilch, Jacek; Fahiminiya, Somayyeh; Abramowicz, Anna; Cristian, Ingrid; Buscarilli, Michelle; Naslavsky, Michel Satya; Malaquias, Alexsandra C; Zatz, Mayana; et al.
Abstract : Background: Noonan syndrome is an autosomal dominant, multisystemic disorder caused by dysregulation of the RAS/mitogen activated protein kinase (MAPK) pathway. Heterozygous, pathogenic variants in 11 known genes account for approximately 80% of cases. The identification of novel genes associated with Noonan syndrome has become increasingly challenging, since they might be responsible for very small fractions of the cases. Methods: A cohort of 50 Brazilian probands negative for pathogenic variants in the known genes associated with Noonan syndrome was tested through whole-exome sequencing along with the relatives in the familial cases. Families from the USA and Poland with mutations in the newly identified genes were included subsequently. Results: We identified rare, segregating or de novo missense variants in SOS2 and LZTR1 in 4% and 8%, respectively, of the 50 Brazilian probands. SOS2 and LZTR1 variants were also found to segregate in one American and one Polish family. Notably, SOS2 variants were identified in patients with marked ectodermal involvement, similar to patients with SOS1 mutations. Conclusions: We identified two novel genes, SOS2 and LZTR1, associated with Noonan syndrome, thereby expanding the molecular spectrum of RASopathies. Mutations in these genes are responsible for approximately 3% of all patients with Noonan syndrome. While SOS2 is a natural candidate, because of its homology with SOS1, the functional role of LZTR1 in the RAS/MAPK pathway is not known, and it could not have been identified without the large pedigrees. Additional functional studies are needed to elucidate the role of LZTR1 in RAS/MAPK signalling and in the pathogenesis of Noonan syndrome.